(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined the relationship between job preparedness, professional competence, and work efficiency among Administrative Officers in the Department of Education. Using a quantitative descriptive-correlational design, data were gathered from 106 Administrative Officers in the Schools Division of Capiz through a validated survey questionnaire. Frequency counts, percentages, means, standard deviations, Spearman's rho, and other appropriate statistical analyses were used. The findings showed that the respondents demonstrated high levels of job preparedness, professional competence, and work efficiency. More importantly, the results revealed significant positive relationships among the variables. Job preparedness showed the strongest association with professional competence (r = 0.790, p < .01), followed by the relationship between professional competence and work efficiency (r = 0.585, p < .01), and job preparedness and work efficiency (r = 0.552, p < .01). These findings suggest that when administrative officers are better prepared for their roles, they are more likely to demonstrate stronger professional competence, which also contributes to improved work efficiency. The study underscores the value of sustained professional development and organizational support in strengthening administrative performance within the Department of Education.